A digital microfluidic system with integrated electrochemical impedance detection arrays. Issue 1 (1st February 2022) - Jin, Kai; Huang, Qi; Hu, Chenxuan; Hu, Siyi; Li, Jinhua
Abstract: Electrochemical sensing provides a new way for miniaturization and low cost of equipment. Meanwhile, digital microfluidic (DMF) technology is making lab-on-chip a reality. The two technologies are essential in the point-of-care area. Electrochemical detection on electrodes and DMF-based droplet driving electrode realize their respective functions by means of electrical signals. In terms of working mode, it seems to have certain similarity, and electrochemical sensing seems to be more suitable for integrating digital microfluidic systems. We thus integrated electrochemical sensing on an active matrix (AM) DMF system. As a common transparent conductive glass, indium tin oxide (ITO) has been widely used as the top plate of the digital microfluidic chip. In this work, we used ITO glass with patterned interdigital electrodes as the top plate of the AM-DMF chip. We achieved on-chip droplet volume detection by electrochemical impedance spectroscopy (EIS). We also proposed a novel sample dilution method on the DMF chip. It takes only 30 seconds to dilute solutions into 4 different concentrations. We then analyzed droplet samples of different concentrations with EIS method. And the correlation coefficient of the fitted curve is as high as 0.9964. In conclusion, EIS is a powerful detection technology for fast, high-integration and low-cost detection on DMF system. The integration of EIS and DMF can be used in various biochemical analyses in the future.